Dangla-Migama and Afro-Asiatic II: Bidiya Č- and Ǯ- - Takács, Gábor (Lingua Posnaniensis, 2010)
The paper represents at once a retarded, albeit detailed review article of the 1989 Bidiya vocabulary by Khalil Alio and a contribution to the etymological analysis of the Dangla-Migama language group (spoken in the western part of the Republic of Chad), where also Bidiya belongs, part of the Chadic language family (and, thus, ultimately, of the vast Afro-Asiatic macrofamily).